Effect of adjuvant radiotherapy after breast-conserving surgery in elder women with early-stage breast cancer: a propensity-score matching analysis - Han, Tingting; Shi, Mingwei; Chen, Qiwei; Chen, Dongbo; Hao, Jiqing (Frontiers in Oncology, 2023)
Purpose: The study aimed to explore the role of adjuvant radiotherapy (RT) after breast-conserving surgery (BCS) in elder women with early-stage breast cancer (BC). Methods: BC patients with 70-79 years of age, stage T1‐2N0‐1M0, undergoing BCS were screened in the Surveillance, Epidemiology and End Results (SEER) database between 2010 and 2015. The clinicopathological characteristics were balanced with propensity-score matching (PSM) method. Kaplan–Meier curves and Cox regression analyses were performed to determine the impact of adjuvant RT on BC patients. Results: Ultimately, 12,310 patients treated with adjuvant RT and 4837 patients treated with no RT, were involved in the analysis. Overall, patients treated with adjuvant RT was associated with a better breast cancer-specific survival (BCSS) (HR: 1.980 [1.596- 2.456], P < 0.001) and overall survival (OS) (HR: 2.214 [1.966- 2.494], P < 0.001) than those who did not undergo RT. After 1:1 PSM, adjuvant RT still performed advantage in both BCSS (HR: 1.918 [1.439- 2.557], P < 0.001) and OS (HR: 2.235 [1.904- 2.624], P < 0.001). In the multivariate COX analysis of BCSS, widowed, divorced and separated patients, tumor grade III, T2 stage, N1 stage, no RT, molecular subtypes with luminal B and triple negative were associated with a shorter BCSS (P < 0.05). In the multivariate COX analysis of OS, age ≥74 years, widowed, divorced and separated patients, tumor grade II/III, T2 stage, no RT, no chemotherapy, molecular subtypes with triple negative were associated with a shorter OS (P < 0.05). Furthermore, the advantages of adjuvant RT were observed in all subgroup analysis. Conclusion: Adjuvant RT after BCS can improve both BCSS and OS in elderly patients with early-stage BC. Additionally, all subgroups analysis-derived BCSS and OS were in support of RT.